2010
DOI: 10.1089/dia.2009.0163
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Metabolic Abnormalities in Offspring of Subjects with Diabetes Mellitus

Abstract: Children from families with type 2 diabetes are at increased risk for obesity. Risk increases by fivefold when both parents have diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…7,8 Studies carried out in different populations and ethnic groups reported high prevalence of obesity and metabolic abnormalities in offspring of diabetic parents, predisposing them at the risk of developing diabetes. 11,22,21 In our study 19% of the subjects (age 15 -25 years) with FHD are obese which is in consistent with the study reported recently from India but lower when compared with 26,27 studies from Eastern Europe and Middle East. When parental consanguinity was also considered along with FHD the prevalence of obesity increased to 24% which showed the effect of parental consanguinity on metabolic disturbances in the offspring.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7,8 Studies carried out in different populations and ethnic groups reported high prevalence of obesity and metabolic abnormalities in offspring of diabetic parents, predisposing them at the risk of developing diabetes. 11,22,21 In our study 19% of the subjects (age 15 -25 years) with FHD are obese which is in consistent with the study reported recently from India but lower when compared with 26,27 studies from Eastern Europe and Middle East. When parental consanguinity was also considered along with FHD the prevalence of obesity increased to 24% which showed the effect of parental consanguinity on metabolic disturbances in the offspring.…”
Section: Discussionsupporting
confidence: 92%
“…7,8 Evidence is available suggesting disturbances of carbohydrate and lipid metabolism in individuals with a history of T2DM in first degree relatives. [9][10][11][12] Previous studies reported higher fasting plasma glucose (FPG) in non-diabetic males with a FHD as compared to those with no FHD. 13,14 A study reported that Asian Indian adolescents with both diabetic parents had high FPG was as compared to one diabetic parent.…”
Section: Original Articlementioning
confidence: 99%
“…Our sampling frame was ‘Offspring of individuals with diabetes study’ database (Praveen et al ., ). There were 358 subjects who had family members (parent or grandparent) with type 2 diabetes mellitus (T2DM) and 287 subjects who did not have family history of T2DM, recruited for the study.…”
Section: Methodsmentioning
confidence: 97%
“…Our sampling frame was the “Offspring of individuals with diabetes study” database 12. There were 358 offspring of individuals with type 2 diabetes mellitus (T2DM) and 287 controls (individuals who did not have a family history of T2DM) recruited for the study.…”
Section: Methodsmentioning
confidence: 99%